Strike in Portugal: Perception differences between public and private sector employees - Ribeiro, Diamantino (2019)
At a time when strikes are once again very frequent in Portugal, especially in sectors with a predominance of public management – in spite of the international recognition of the good performance of the Portuguese economy – an enquiry was developed in order to evaluate if there are differences between the perception and action of workers in the public sector and the private sector about strike. A survey conducted on Google Drive platform between November 28, 2017 and January 16, 2018. A total of 1071 responses were obtained. Fifteen questions were asked to obtain the respondents profile: age, sex, marital status, educational qualifications, employment status, type of organization where you work, sector, length of service in the current job, type of contract, occupation, place of residence, place of work, size of organization and place of birth. At the same time, quantitative questions were asked regarding the perception of the strike, unionism, social manifestations and the impact of strikes on the society. The questions that the study intends to answer are: 1) Do workers in public departments think and act differently from private sector workers towards strikes? 2) Do the workers question their right to strike? 3) Does the Portuguese population understand that workers in the public sector benefit from the right to strike? 4) What is the understanding of the positioning of the private sector in relation to the strike? 5) Are consecutive union-led strikes well accepted and understood by the general population? 6) Can it be verified that Portuguese workers defend some rules and limitations in the right to strike? We respond to these questions through respondents' opinions on the 15 survey questions. Based on data from the "PORDATA" platform for the year 2017, the total population in Portugal was 10,325,453 people. The active population corresponded to 5,178,300 (50.2%), of which 4,514,502 (87.2%) worked in the private sector and 663,798 (12.8%) in the public sector, representing 6.43 % of total population. Considering that the sample size (1,071 respondents) is composed of 209 public employees, (19.5% of the respondents), the authors are of the opinion that the results obtained are representative of the Portuguese population. The results indicate that: a) There are no substantial differences in the perception of the strike between civil servants and private employees; b) The majority of the respondents, defends the right to strike, but not the duty; c) Express the view that workers should not be able to use the strike in any circumstance, showing concern with the population in general; d) Understand that workers should find other alternatives to fight for their rights without causing prejudice of the population at large; e) More than half of the respondents are of the opinion that the reasons for the strikes are not perceptible by the population.The results justify the continuation of the research on strike with the aim of finding, evaluating and considering other forms of fight in order to reduce the use of the strike and the negative impacts that it causes in the general population.